Magnetic Levitation Training Kit For Teaching Basic Electrical Control System Courses - Mohd Ab Halim, Mohd Firdaus; Yahaya, Muhammad Sharil; Ibrahim, Zulkifli; Hj Md Basar, Mohd Farriz; Mohamad Sapiee, Mohd Razali; Ahmad, Suziana; Che Wan Mohd Zalani, Che Wan Mohd Faizal; Salim, Fadzilah; Noordin, Aminurrashid; Ibrahim, Norliana (2012)
In this paper, we propose a training kit for developing a system to assist basic electrical control courses to the undergraduate students of Electrical Engineering or Electrical Engineering Technology. We present magnetic levitation hardware demonstrating a load hanging in the air with the help of electromagnetic coil. The students are provided with unassembled training kit project where they will use it to achieve several learning outcome. Technical data of the system is given along with a basic instruction manual as benchmark for the training kit. The magnetic levitation kits provide an open-ended design problem such as designing a sensor, load, closed loop feedback system and a lot more. The training kit is alter made to provide exciting and excellent teaching tools for controls system subject unlike the conventional trainer module.